2022
DOI: 10.1055/s-0042-1747935
|View full text |Cite
|
Sign up to set email alerts
|

Post-Intensive Care Syndrome in a Cohort of School-Aged Children and Adolescent ICU Survivors: The Importance of Follow-up in the Acute Recovery Phase

Abstract: Pediatric intensive care unit (PICU) survivors experience a collection of physical, cognitive, emotional, and social symptoms named post-intensive care syndrome (PICS). We aimed to quantify PICS morbidities from multiple stakeholder perspectives across domains. Using physician, neuropsychologist, and parent/caregiver-completed outcome measures across domains in a cross-sectional analysis of 186 children between the ages of 8 and 19 years with data from a PICU follow-up clinic 1 to 3 months after PICU discharge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 63 publications
(100 reference statements)
1
7
0
Order By: Relevance
“…[8][9][10][11][12][13][14][15][16][17][18] A recent study showed that more than a quarter of school-aged children and adolescents with ABI after PICU discharge met the diagnostic criteria for a new diagnosis of a neurocognitive disorder on expert evaluation, with the majority (66%) exhibiting concerns on evaluation not rising to the level of diagnosis but prompting need for additional clinical follow-up. 19 Consistent with prior research literature, the aforementioned study highlighted the potential for cognitive morbidity related to ABI within the executive functioning system. Considering executive functioning as a vital cognitive outcome is important because of its association with adaptive skill development, personality characteristics, social relationships, behavioral regulation, learning, and academic achievement in ABI survivors.…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…[8][9][10][11][12][13][14][15][16][17][18] A recent study showed that more than a quarter of school-aged children and adolescents with ABI after PICU discharge met the diagnostic criteria for a new diagnosis of a neurocognitive disorder on expert evaluation, with the majority (66%) exhibiting concerns on evaluation not rising to the level of diagnosis but prompting need for additional clinical follow-up. 19 Consistent with prior research literature, the aforementioned study highlighted the potential for cognitive morbidity related to ABI within the executive functioning system. Considering executive functioning as a vital cognitive outcome is important because of its association with adaptive skill development, personality characteristics, social relationships, behavioral regulation, learning, and academic achievement in ABI survivors.…”
Section: Introductionsupporting
confidence: 82%
“…The rationale for use of the mentioned assessments as part of standard care in the acute recovery phase for ABI has been previously reported. 19,70,71,77…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, no standardized structure for follow-up care after PICU admission exists. Current PICU follow-up programs (11)(12)(13)(14)(15)(16)(17) vary widely with respect to, among others, the included patients, involved health care professionals, follow-up moment(s), and assessed outcomes. Moreover, most PICU follow-up programs lack structured data collection (11), which is essential for health care evaluation and scientific research on outcome and prognosis of critically ill children.…”
Section: Discussionmentioning
confidence: 99%
“…Given the distinct heterogeneity of the PICU population and potential consequences in a wide range of outcome domains, the prognosis after PICU admission is uncertain, in turn challenging clinical follow-up. Currently, a few descriptions of PICU follow-up programs have emerged in the literature (11)(12)(13)(14)(15)(16)(17). To our knowledge, no standardized structure for follow-up care after PICU admission exists.…”
mentioning
confidence: 99%